(untitled) (International Journal of Automation and Smart Technology, 2014)
This paper describes a light-addressed electrolytic system used to electrodeposit polysaccharide chitosan membranes on a photoconductive substrate using a digital micromirror device (DMD). In this system, a patterned-light illumination is projected onto a photoconductive substrate serving as a photo-cathode to electrolytically produce hydroxide ions, which leads to an increased pH gradient. The high pH generated at the cathode can cause a local gelation of chitosan through sol-gel transition. Controlling the illumination pattern on the DMD allowed for the light-addressed electrodeposition of chitosan membranes with different shapes and sizes, as well as multiplexed micropatterning. Experiments were performed to assess the effect of illumination time of the light pattern and the effect of the applied current density on the dimensional resolution of chitosan membrane formation. The spatial resolution in our proposed method was demonstrated to be about 40 m by patterning with a variety of line-widths and gap distances. We anticipate that photo-electro-chemically-induced deposition of chitosan-based hydrogels may offer interesting opportunities for the integration of biological systems into miniaturized devices.